PEMBERDAYAAN MASYARAKAT SUKU TALANG MAMAK DALAM BUDIDAYA MADU KELULUT DI KAWASAN TAMAN NASIONAL BUKIT TIGA PULUH INDRAGIRI HULU - Herman; Rosmita; Rido Idham (ASKETIK: JURNAL AGAMA DAN PERUBAHAN SOSIAL, 2022)
The community empowerment program in the Bukit Tigapuluh National Park area in the cultivation of kelulut honey is a community empowerment program created and managed directly by the Bukit Tigapuluh National Park Office with the target recipient of the program being indigenous people living in this national park area, such as the Talang Mamak Tribe community with the aim of providing empowerment activities so that the community can earn additional income to meet their economic needs. This study aims to analyze and explain how the Talang Mamak Tribe Community Empowerment in the Bukit Tiga Puluh National Park Area in Cultivating Kelulut Honey in Rantau Langsat Village, Batang Gansal District, Indragiri Hulu Regency. This type of research is qualitative by collecting interview and observation data with respondents, namely Balai TNBT and related agencies and the TNBT fostered Forest Farmers Group. In this study, it was found that the implementation of the program had been implemented but not optimal as a whole due to several indicators used in this study such as standards and targets, resources, communication between organizations, and characteristics of implementers. , socio-economic environment and attitude of implementers in program implementation. Not all of the implementation processes of this empowerment program are in the implemented category so that everything is still not maximally implemented.